2018
DOI: 10.1016/j.dib.2018.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance data of 6 Asian economies (2010–2017)

Abstract: This article contains firm-level data on 1) aggregated corporate governance score, and 2) financial data for the period 2010–2017. The study includes 626 companies from 6 Asian countries: China, India, Indonesia, Japan, South Korea and Thailand. Aggregated corporate governance score is calculated using 13 firm-level attributes: board size, board independence, CEO duality, board meeting attendance, independence of audit committee, auditor ratification, independence of compensation committee, independence of nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…However, causal connections of economic growth are studied insufficiently and are not determined by modern economic science, requiring further research. The issues of corporate management are explored in the works of such scholar as Al-Hadi et al (2018) , Bae et al (2018) , Ben-Hassoun et al (2018) , Bobillo et al (2018) , Gaitán et al (2018) , Jacometti et al (2019) , Keay and Zhao (2018) , Marques et al (2018) , Marquis et al (2017) , Oh et al (2018) , Singareddy et al (2018) , and Thomsen (2016) . The existing publications reflect the essence and methodological approaches to corporate management.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, causal connections of economic growth are studied insufficiently and are not determined by modern economic science, requiring further research. The issues of corporate management are explored in the works of such scholar as Al-Hadi et al (2018) , Bae et al (2018) , Ben-Hassoun et al (2018) , Bobillo et al (2018) , Gaitán et al (2018) , Jacometti et al (2019) , Keay and Zhao (2018) , Marques et al (2018) , Marquis et al (2017) , Oh et al (2018) , Singareddy et al (2018) , and Thomsen (2016) . The existing publications reflect the essence and methodological approaches to corporate management.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…After downloading the annual reports of the firms, the next step was to screen out and extract the information of BOD attributes from annual reports to excel file similar to the methods adopted in the following studies [ 3 , 4 ] the board related information in annual reports were found in company information, directors’ reports to shareholders, directors’ profiles and statements of compliance. Following the aforementioned method, and screening out 1890 annual reports, we have formed an unbalanced panel dataset of 315 non-financial firms in Excel consisting of BOD variables such as Board Size, Board Meetings, Board Independence, Board Female Directorship, Board Expert Directors, CEO Duality, CEO Expertise, audit committee independence and audit committee expertise for the 6 years data period ranging from 2014 to 2019.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%